Geohazard features of the Central-Southern Tyrrhenian seamounts - Michael Marani; Fabiano Gamberi; Elisa Leidi; Alessandra Mercorella; Marzia Rovere; Valentina Ferrante (Journal of Maps)
The Magic project (MArine Geohazard along Italian Coasts), a large coordinated initiative that involved the whole marine geological research community in Italy in 2007–2013, produced a series of maps of the Geohazard features of the Central-Southern Tyrrhenian Seamounts. The features derive from multibeam surveys and therefore mainly rely on the morphological expression of seafloor and shallow sub-surface processes and events. Potential geohazards related to eruption and flank instability of the volcanic seamounts of the Tyrrhenian Sea are discussed and compared.